2013
DOI: 10.3126/kumj.v10i2.7347
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Care Seeking Behavior of Obstetric Complication in Thailand

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This study revealed that some of the women who reported complications did not seek services due to reasons, like did not see seriousness of the problems, seen as not necessary, and because family did not allow to seek assistance. These finding agreed with the findings outside Ethiopia [ 7 , 12 , 22 ], but differed with the previous findings of home study [ 9 ] and outside [ 11 ] in that inability to judge the graveness of condition, distance/transport problems, lack of money/cost considerations, and use of traditional options at home, inadequate training of health personnel and lack of health insurance were observed. These differences may be due to cultural differences of inhabitants from region to region with in the home country and some cultural similarities of home country with outside home to influence on not to seek assistance to pregnancy complications.…”
Section: Discussionsupporting
confidence: 82%
“…This study revealed that some of the women who reported complications did not seek services due to reasons, like did not see seriousness of the problems, seen as not necessary, and because family did not allow to seek assistance. These finding agreed with the findings outside Ethiopia [ 7 , 12 , 22 ], but differed with the previous findings of home study [ 9 ] and outside [ 11 ] in that inability to judge the graveness of condition, distance/transport problems, lack of money/cost considerations, and use of traditional options at home, inadequate training of health personnel and lack of health insurance were observed. These differences may be due to cultural differences of inhabitants from region to region with in the home country and some cultural similarities of home country with outside home to influence on not to seek assistance to pregnancy complications.…”
Section: Discussionsupporting
confidence: 82%
“…In the study done in Thailand, the constraints hindering them from seeking care for the complications were perceived to be the lack of access to health personnel, health facilities, and proper transportation. 13 There are differences in healthcare-seeking behaviour across religion. Orthodox Christian households are more likely to seek modern high level care earlier as compared with Muslim-headed households.…”
Section: Discussionmentioning
confidence: 99%
“…People who were close to health post location were found to seek modern treatment more than people who were far away reasoning distance as a main reason for not visiting the health centers. 8 Study done in Thailand by Sharma SK 14 and a study done on reproductive tract infections among women by Puthuchira R AK in India 15 also concludes distance to health facility, poor transportation, and poor health facilities besides other factors as the main reasons for not seeking appropriate care. The distance of health center more than 30 minutes (adj.…”
Section: Distance Of Health Center and Means Of Transportationmentioning
confidence: 99%